Evaluation of Agricultural Byproducts and Cover Crops as Anaerobic Soil Disinfestation Carbon Sources for Managing a Soilborne Disease Complex in High Tunnel Tomatoes - Testen, Anna L.; Rotondo, Francesca; Mills, Matthew P.; Horvat, Madeline M.; Miller, Sally A. (Frontiers in Sustainable Food Systems, 2021)
Anaerobic soil disinfestation (ASD) is a viable option for disease management in tomato production and reduces damage due to a soilborne disease complex consisting of Pyrenochaeta lycopersici, Colletotrichum coccodes, Verticillium dahliae, and Meloidogyne spp. There are plentiful options for ASD carbon sources using byproducts of Midwestern United States agriculture or cover crops, yet these carbon sources have not been evaluated for use in Midwestern settings. Low (10.1 Mg/ha) and high (20.2 Mg/ha) rates of corn gluten meal, distillers dried grains, soybean meal, wheat bran, and dry sweet whey were evaluated as ASD carbon sources in growth chamber and greenhouse bioassays. Cover crops including buckwheat, cowpea, crimson clover, mustard, oilseed radish, sorghum-sudangrass, white clover, and winter rye were evaluated in similar bioassays with one amendment rate (20.2 Mg/ha). Reducing conditions developed in soils regardless of carbon source or rate. Use of high rates of corn gluten meal, distillers dried grains, soybean meal, and wheat bran led to the lowest levels of root rot severity compared to non-treated controls. The higher rate of any byproduct carbon source was always more effective than the lower rate in reducing root rot severity. Use of both rates of soybean meal or corn gluten meal and the high rate of distillers dried grains or dry sweet whey led to significant increases in dry root and shoot biomass compared to controls. For cover crops, ASD with crimson clover, sorghum-sudangrass, white clover, or winter rye amendments reduced root rot severity relative to the aerobic control, but not relative to the anaerobic control. Use of cover crops did not significantly impact plant biomass. A subset of three ASD carbon sources [distillers dried grains, soybean meal, and wheat middlings (midds), all 20.2 Mg/ha] were evaluated in five on-farm ASD trials in high tunnels. Soil temperatures were low during the application period, limiting treatment efficacy. Reducing conditions developed in all soils during ASD treatment, and a moderate but significant reduction in root rot severity was observed following ASD with the soybean meal or wheat midds compared to ASD with distillers dried grains. Tomato yield was not significantly affected by ASD treatment.